Antibody level dynamics until after the third dose of COVID-19 vaccination - Nanae Asahi; Ippei Sakamaki; Yukio Hida; Kunio Torii; Norikazu Hashimoto; Hiromichi Iwasaki; Masayuki Iwano; Hideki Kimura (Heliyon, 2023)
The antibody titers of volunteers, including elderly people, were investigated after the second dose of the BNT162b2 vaccine (Pfizer-BioNTech) as an mRNA vaccine against the coronavirus disease 2019 (COVID-19). Serum samples were collected from 105 volunteers (44 healthcare workers and 61 elderly people) 7–14 days after the second vaccine dose, and antibody titers were measured. The antibody titers of study participants in their 20s were significantly higher than those of other age groups. Furthermore, the antibody titers of participants aged <60 years were significantly higher than those of participants aged ≥60 years. Serum samples were repeatedly collected from 44 healthcare workers until after the third vaccine dose. Eight months after the second round of vaccination, the antibody titer levels decreased to the same level as that before the second vaccine dose. After the third booster vaccination, the antibody titer recovered to the same level as that after the second dose. Neutralizing activities were also investigated at four time points before and after the second vaccine dose. The antibody titers and neutralizing activity were positively correlated. Therefore, neutralizing activity can be predicted by measuring the antibody titer. In conclusion, the antibody titers in the elderly population were significantly lower than those in the younger population. Although the antibody titers increased following vaccination, their levels showed a decline after several months, returning to the same level as that after a single dose of mRNA vaccination. The antibody titer levels recovered after the third dose of vaccination, which had already been administered in Japan. Routine administration of vaccine should be considered in the future.